An investigation into the prevalence of knowledge management practices within the libraries of two institutions on the verge of a merger : Cape Technikon and Peninsula Technikon - Khangala, Busisiwe Nobuhle (Stellenbosch : University of Stellenbosch, 2011)
Assignment (MA)--University of Stellenbosch, 2004.